Formation of professional competences of students-foreigners when studying the Russian language discipline - Ilkhamiya I. Galimzyanova; Sazida V. Vyugina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The material on the problems of the formation of professional competencies of foreign students of a non-linguistic university while studying the discipline "Russian as a foreign language" is presented. The features of the formation of communicative competence in the classroom are described in detail with a personality-oriented approach in the process of learning the Russian language as a foreign language. In the educational process with foreign students, a special place is occupied by professionally oriented reading. The methodology of teaching Russian as a foreign language presents different types of reading. The methods of studying, familiarization and viewing types of reading are described in detail, which are relevant in the study of Russian as a foreign language. In the process of formation and development of the communicative competence of foreign students, attention should be paid to the learning objectives, the content of the educational material, to focus on the professional motivation of students needed to develop communication skills and abilities, to communicate with teachers of special disciplines. The teacher should take into account that when teaching a language, it is important to include such approaches to modern students in the educational process in order to obtain high-quality results that they could subsequently use in their professional activities. The paper notes the need to choose professionally-oriented textual material for reading, which is so necessary for foreign students. According to the authors of the article, professionally oriented reading is both a goal and a means of teaching Russian to foreign students, as well as the need to familiarize students with the original literature in the specialty in order to successfully apply the knowledge and skills acquired in the Russian language classes in the educational process.